Embryonic Expression of NrasG 12 D Leads to Embryonic Lethality and Cardiac Defects - You, Xiaona; Ryu, Myung-Jeom; Cho, Eunjin; Sang, Yanzhi; Damnernsawad, Alisa; Zhou, Yun; Liu, Yangang; Zhang, Jing; Lee, Youngsook (Frontiers in Cell and Developmental Biology, 2021)
Ras proteins control a complex intracellular signaling network. Gain-of-function mutations in RAS genes lead to RASopathy disorders in humans, including Noonan syndrome (NS). NS is the second most common syndromic cause of congenital heart disease. Although conditional expression of the NrasG12D/+ mutation in adult hematopoietic system is leukemogenic, its effects on embryonic development remain unclear. Here, we report that embryonic expression of endogenous NrasG12D/+ in mice caused embryonic lethality since embryonic day (E) 15.5 and developmental defects predominantly in the heart. At E13.5, NrasG12D/+; Mox2Cre/+ embryos displayed a moderate expansion of hematopoietic stem and progenitor cells without a significant impact on erythroid differentiation in the fetal liver. Importantly, the mutant embryos exhibited cardiac malformations resembling human congenital cardiac defects seen in NS patients, including ventricular septal defects, double outlet right ventricle, the hypertrabeculation/thin myocardium, and pulmonary valve stenosis. The mutant heart showed dysregulation of ERK, BMP, and Wnt pathways, crucial signaling pathways for cardiac development. Endothelial/endocardial-specific expression of NrasG12D/+ caused the cardiac morphological defects and embryonic lethality as observed in NrasG12D/+; Mox2Cre/+ mutants, but myocardial-specific expression of NrasG12D/+ did not. Thus, oncogenic NrasG12D mutation may not be compatible for embryonic survival.